Processo de ensino da dança folclórica alemã na perspectiva colaborativa e universalista - Silva, Bruna Poliana (Universidade Federal de São Carlos, 2025)
Folk dance is a cultural expression that plays an important role in shaping a people’s identity and has the potential to enrich the educational process. This study aimed to develop and analyze, from a universalist perspective, the teaching process of German folk dance in a collaborative framework, valuing diversity and universalist practices. The specific objectives were: a) to verify how dance is included as a curricular component from the perspective of the participating teachers; b) to analyze the collaborative development of the German folk dance teaching process with the teachers; c) to examine the applicability of this teaching process in the perspective of diversity and universalist practices; and d) to verify the level of collaboration among teachers in the development and implementation of the teaching process. This is an intervention study, within the perspective of collaborative research, with a qualitative approach, involving four teachers (Physical Education, Music, Special Education, and the classroom teacher) and 28 students from a 5th-grade class, including one with autism spectrum disorder. Data collection included interviews, classroom observations, analysis of teacher collaboration in planning and implementation, as well as records of the development, implementation, and evaluation stages. Three planning meetings and one evaluation meeting were conducted, culminating in the implementation of 11 interdisciplinary lessons in Geography, Arts, Music, and Physical Education. These lessons were observed by the researcher, recorded in video and field notes, and concluded with a presentation for the school community. Data, analyzed through thematic analysis, were organized into four axes: diagnostic survey, collaborative planning, implementation, and evaluation. German folk dance, integrated into the curriculum in a collaborative and interdisciplinary way, was recognized as a legitimate and enriching content, capable of promoting meaningful learning, broadening student participation, and fostering inclusion. Strengthening of belonging, engagement, and the integration of cultural, motor, and social content were observed. Three central themes emerged: Dance as curricular content, highlighting its formative potential and cultural value; Planning and implementation, marked by interdisciplinary articulation and teacher collaboration; and Evaluation, which emphasized inclusion as a natural outcome of universalist planning. Teacher collaboration was characterized by joint decision-making, flexibility, and adaptation to student needs, although greater integration across disciplines remains a challenge. External evaluators confirmed pedagogical coherence, methodological clarity, and diversity of strategies as strong points. Conclusion: the developed model proved feasible and replicable, serving as a reference for inclusive, culturally meaningful, and universalist-aligned educational practices.
Teaching process of german folk dance from a collaborative and universalist perspective
Keywords: Educação especial; Ensino colaborativo; Processo de ensino; Dança Folclórica Alemã; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade